2016
DOI: 10.3109/19401736.2015.1137898
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and geographic differentiation in butter catfish, Ompok bimaculatus , from Indian waters inferred by cytochrome b mitochondrial gene

Abstract: Documentation of genetic differentiation among the populations of a species can provide useful information that has roles in conservation, breeding, and management plans. In the present study, we examined the genetic structure and phylogenetic relationships among the 149 individuals of Ompok bimaculatus belonging to 24 populations, collected from Indian waters, using cytochrome b gene. The combined analyses of data suggested that the Indian O. bimaculatus consist of three distinct mtDNA lineages with star-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The cytochrome b gene has been used to evaluate the fish genetic diversity and phylogeny. Investigations across closely related species are viable because CYT B markers develop fast (Zhu et al 2016;Kumar et al 2017;Megarani et al 2020;Ibrahim 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The cytochrome b gene has been used to evaluate the fish genetic diversity and phylogeny. Investigations across closely related species are viable because CYT B markers develop fast (Zhu et al 2016;Kumar et al 2017;Megarani et al 2020;Ibrahim 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al (2019) used morphometrics and cytochrome b (cyt b) sequence to demonstrate the distinctiveness between P. paranae and P. rivularis Lütken, 1875, both formerly subspecies of P. scabripinnis from Upper Parana and São Francisco river basins, respectively. Kumar et al (2017) also used cytB to show three mitochondrial lineages with high genetic variation and haplotypic diversity in Ompok bimaculatus Bloch, 1974. Using the same tool, Zhu et al (2016) found moderate to high levels of genetic differentiation in 11 populations of Scomber japonicus Houttuyn, 1782, with two of them well structured, showing high diversity besides the other nine with low ones.…”
Section: Methodsmentioning
confidence: 99%
“…Cyt b gene has been preferred for both in-species and interspecific variations in many studies (Berrebi, 1995;Callejas and Ochando, 2002;Kartavtsev and Lee, 2006;Sakai et al, 2009;Markovà et al, 2010;Zheng et al, 2016;Behera et al, 2017;Kumar et al, 2017). There are some studies about genetic structure of Barbus species from different regions performed on understanding the phylogeny among the species.…”
Section: Discusionmentioning
confidence: 99%
“…The results of AMOVA showed the presence of high (40.69%) within population variation which favored the haplotype differentiation. Livi et al (2013) evaluated the molecular and morphometric properties of the Barbus species sampled from Italy and reported 29.80% of Barbus spp. diversity within populations and 63.78% among groups.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation